“PE WITH THE CLASS” starts in the family Parent – the initiator of the motor activity in the family - Piech, Krzysztof; Bodasińska, Anna (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
The motor activity of children and teenagers is dependent on many various factors, mainly on the attitude of parents and class tutors. Increasing aversion of the younger generation to the motor activity, manifested by not being involved in PE lessons should alarm the environment responsible for bringing up the youngsters. Due to this, there is a need to seek for models of the activity which will contribute to the change of negative trends.The aim of this article is to show the family as an important part of a recreation education circle, as well as introducing the models of the motor activity in the family. Suggested models have been evaluated by the families being part of them. It was also decided to check if they are accurate proposals, having a chance of a wider social reception, and if they reach parents and children’s expectations.Achieved results indicate the need for recognizing the family as an important link in the process of introducing younger generation to an active lifestyle and the need for emphasizing the extremely substantial role of parents in preparing pre-school aged children for their future, active participation in physical education lessons.